2017
DOI: 10.1007/s40333-017-0024-4
|View full text |Cite
|
Sign up to set email alerts
|

Time lag characteristics of sap flow in seed-maize and their implications for modeling transpiration in an arid region of Northwest China

Abstract: Plant capacity for water storage leads to time lags between basal stem sap flow and transpiration in various woody plants. Internal water storage depends on the sizes of woody plants. However, the changes and its influencing factors in time lags of basal stem flow during the development of herbaceous plants including crops remain unclear. A field experiment was conducted in an arid region of Northwest China to examine the time lag characteristics of sap flow in seed-maize and to calibrate the transpiration mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 83 publications
(106 reference statements)
1
7
0
Order By: Relevance
“…Among the three radiative energy variables included in this research (R s , R n , PAR), we found that PAR had the maximum correlation with T LAI -1 across all crops, which was substantially greater than R s and R n (table 2). In the literature, maize transpiration has been shown to be driven by R s (Bo et al, 2017;Rousseaux et al, 2009), but PAR showed the most energy driving effect. PAR represents the visible portion (400-700 nm) electromagnetic spectrum that is useful for plant growth and development and thus is a better predictor of T LAI -1 than R s .…”
Section: Radiative Energy Indicators (Rs Rn Par) As Drivers Of Crop T...mentioning
confidence: 99%
“…Among the three radiative energy variables included in this research (R s , R n , PAR), we found that PAR had the maximum correlation with T LAI -1 across all crops, which was substantially greater than R s and R n (table 2). In the literature, maize transpiration has been shown to be driven by R s (Bo et al, 2017;Rousseaux et al, 2009), but PAR showed the most energy driving effect. PAR represents the visible portion (400-700 nm) electromagnetic spectrum that is useful for plant growth and development and thus is a better predictor of T LAI -1 than R s .…”
Section: Radiative Energy Indicators (Rs Rn Par) As Drivers Of Crop T...mentioning
confidence: 99%
“…Prior studies have noted the importance of both soil moisture and meteorological demands in controlling time lags [22,40,41]. However, most studies in the field have only focused on the influence of VPD on time lags while neglecting the effects of comprehensive meteorological factors, such as ET ref , that directly reflect evapotranspiration demand.…”
Section: Influence Of Environmental Factors On Variations In Time Lagmentioning
confidence: 99%
“…For instance, Zeppel et al [22] pointed out that declines in soil moisture along with declines in soil-root conductance could lead to larger hysteresis on drier days; however, Wullschleger et al [23] reported that hysteresis was more evident in wet soils. Bo et al [41] noted that the effects of dry soil on lag times in sap flow may not be straightforward since the soil moisture deficit generally affects plant stem flow at different temporal scales than the main environmental factors of stem flow. Zhang et al [12] noted that the shape of the hysteresis loop was primarily controlled by the time lag between radiation and VPD at high soil moisture levels and that the soil moisture content affected J s -VPD hysteresis under water stress, which was defined as θ < 0.175.…”
Section: Influence Of Environmental Factors On Variations In Time Lagmentioning
confidence: 99%
“…In addition, many papers have reported the existence of periodic and seasonal delays between evapotranspiration and meteorological factors. Bo studied the time-lag characteristics of seed-maize liquid flow and believed that the time-lag of maize liquid flow was significantly different in different growth stages [28] .…”
Section: Time Lag Effect Between Et0 and Meteorological Factorsmentioning
confidence: 99%